Comparative Study on Vegetative and Reproductive Development between Weedy Rice Morphotypes and Commercial Rice Varieties in Perak, Malaysia - Quazi Nasim Ahmed,; PMD Zainudin Hussain ,; Ahmad Sofiman Othman, (Tropical Life Sciences Research, 2012)
This study was conducted to examine the variabilities in the chronology of vegetative and reproductive development of weedy rice (Oryza spp.) in comparison with commercial varieties. Data at different growth stages of 14 weedy rice morphotypes and 4 commercial rice varieties were recorded and analysed. Plant height of all weedy rice morphotypes were observed to be significantly higher compared to the commercial varieties at every growth stages; increase in height was between 10–37 cm for weedy rice morphotype, for every 2 weeks. Initial tillering ability at 14 days after planting (DAP) was higher in weedy morphotypes, however all the commercial rice varieties produced significantly higher number of tillers throughout the rest of the vegetative phases. Correlation between plant height and tiller number detected that taller plants produce fewer tillers than shorter plants. Higher leaf area index (LAI) of all weedy morphotypes except PWR01 at early growth stages indicated the vigorous growth of the morphotypes. Weedy rice morphotypes showed a wide range of anthesis and maturity duration. Accessions from the same weedy rice morphotypes were more heterogeneous in the flowering, anthesis and maturity period than the commercial varieties. These traits enables identification of weedy rice morphotypes at their different growth stages in the field. Kajian ini dijalankan untuk memeriksa kepelbagaian dalam kronologi vegetatif dan perkembangan pembiakan padi angin (Oryza spp.) apabila dibandingkan dengan variasi komersial. Data yang diperolehi daripada beberapa peringkat pertumbuhan untuk 14 morfotip padi angin dan 4 variasi padi komersial telah direkod and dianalisa. Ketinggian semua morfotip padi angin telah ditinjau dan didapati wujudnya perbezaan ketara dalam data untuk setiap peringkat pertumbuhan; peningkatan dalam ketinggian tumbuhan adalah di antara 10–37 cm untuk morfotip padi angin untuk setiap 2 minggu. Keupayaan untuk mempunyai berbilang batang semu pada hari ke 14 selepas penanaman (DAP) adalah lebih tinggi untuk morfotip padi angin. Namun begitu, kesemua variasi padi komersial menunjukan peningkatan keupayaan DAP yang lebih ketara sepanjang fasa vegetatifnya. Korelasi antara ketinggian tumbuhan dan bilangan batang semu telah dikesan dan didapati tumbuhan yang lebih tinggi menghasilkan bilangan batang semu yang lebih kurang berbanding tumbuhan yang lebih rendah. Indeks luas daun (LAI) untuk kesemua morfotip padi angin kecuali PWR01 pada peringkat awal pertumbuhan menunjukan pertumbuhan pesat. Morfotip padi angin juga menunjukan kepelbagaian semasa antesis dan durasi matang. Aksesi daripada morfotip padi angin yang sama menunjukan tumbuhan ini lebih heterogen semasa fasa berbunga, antesis dan durasi matang berbanding dengan variasi-variasi komersial. Trait-trait sebegini amat membantu untuk mengenal pasti morfotip padi angin semasa peringkat pertumbuhan yang berbeza di sawah.